Low power and reliable interconnection with combination of Crosstalk Avoidance Green Coding and capacitively charge-sharing transmitter for network-on-chip. (May 2018) - Xu, Changqing; Liu, Yi; Ma, Shuai; Yang, YinTang
Abstract: In this paper, a low power and crosstalk avoidance coding called Crosstalk Avoidance Green Coding (CAGC) is proposed and combined with capacitively charge-sharing transmitter (CCS) to provide reliable and energy-efficient interconnections for network-on-chip (NoC). The proposed CAGC consists of Green Modified Coding (GMC) and Adaptive Temporal Coding (ATC). The GMC achieves more energy reduction by modifying the mapping between original set and converted set. And the ATC reduces crosstalk by transmitting a shielding code in the case of Worst-Case-Crosstalk (WCC). In order to further reduce the power consumption of NoCs, CCS is applied to achieve a swing-voltage reduction to 10% of the supply voltage. Based on SMIC 0.13 μm CMOS technology, the simulation results show that CAGC and CCS can achieve 37.51% and 73% energy reduction compared to the full swing transmitter without low power codec, respectively. However, the combination of CAGC and CCS not only achieves 81% energy reduction, but also increases reliability by improving the ability of crosstalk avoidance. Highlights: A low power and crosstalk avoidance coding for NoC called Crosstalk Avoidance Green Coding (CAGC) is proposed. ATC is proposed to reduce crosstalk by transmitting a shielding code in the case of Worst-Case-Crosstalk. A combination of CAGC and CCS is proposed to reduce the power consumption of NoC and improve the reliability of NoC.